Seamless gene tagging by endonuclease-driven homologous recombination - Khmelinskii, Anton; Meurer, Matthias; Duishoev, Nurlanbek; Delhomme, Nicolas; Knop, Michael (PLOS ONE, 2011)
Gene tagging facilitates systematic genomic and proteomic analyses but chromosomal tagging typically disrupts gene regulatory sequences. Here we describe a seamless gene tagging approach that preserves endogenous gene regulation and is potentially applicable in any species with efficient DNA double-strand break repair by homologous recombination. We implement seamless tagging in Saccharomyces cerevisiae and demonstrate its application for protein tagging while preserving simultaneously upstream and downstream gene regulatory elements. Seamless tagging is compatible with high-throughput strain construction using synthetic genetic arrays (SGA), enables functional analysis of transcription antisense to open reading frames and should facilitate systematic and minimally-invasive analysis of gene functions.
Gesehen am 29.09.2021